Strategic Aspects of Activities Carried Out by the Eurasian Development Bank - Alekseevna Bunich, Galina; Aleksandrovich Rovenskiy, Yuriy; Tambievna Akhvlediani, Julia; Anatolievna Zvonova, Elena (International Journal of Engineering and Technology, 2018)
The modern stage of global financial market development is marked by intensive innovation. One of its peculiarities is quick formation and improvement of activities carried out by international regional development banks.The establishment of international regional development banks happened in the 1960s. During this period, development banks were founded in the countries and regions that got free from colonial dependency.At present, concerted efforts are observed in the sector of international regional development banks.During half a century of the activities, the mission, goals and operating principles of international regional development banks have changed conspicuously. Now their priorities are to finance long-term programs of regional infrastructure development, to invest in global projects and to lend socio-economic development programs.Along with earlier established international regional development banks, new institutions are also created. The primary reason for the establishment of these financial institutions is a regionâ€™s need to draw global investment.One of the newly established regional development banks is the Eurasian Development Bank that substantially differs from banks in operation. The Bankâ€™s primary specific features are the parity compliance with the interests of the regionâ€™s countries and the attainment of socio-economic tasks related to the regionâ€™s development.Â Â